Food Expenditure and GST in New Zealand - Christopher Ball; John Creedy; Michael Ryan (New Zealand Government, The Treasury, 2014)
This paper has two main aims. First, the poor targeting of a policy of zero-rating food in a goods and services tax (GST) is illustrated in a simple model where the revenue lost from zero-rating food is instead devoted to a universal transfer payment, with a larger effect on progressivity. Second, the paper investigates the welfare effects on New Zealand households of zero-rating food. The detailed effects, for a range of household types, are then investigated using Household Economic Survey data. Demand responses to consumer price changes are estimated and welfare changes, in terms of equivalent variations, are obtained. Comparisons are made across `clusters', consisting of groups of households with similar characteristics. The reform is seen to produce a very small amount of progressivity in the GST, with redistribution from richer households without children to poorer households with children, and older households.
Keywords: H31; I3; D11; 330; Umsatzsteuer; Steuerprogression; Steuereinnahmen; Wohlfahrtsanalyse; Neuseeland